NONMETALLICS IN STEELS OF GRADES 80 AND 42Cr4Mo2 - S. V. Stefanovich; V. M. Pishch (Литьë и металлургия)
The nonmetallics in the samples of 10 meltings of steel of grade 80 and 42Cr4Mo2 before and after vacuumization are investigated.